Genome assembly of the Australian black tiger shrimp (Penaeus monodon) reveals a novel fragmented IHHNV EVE sequence - Roger Huerlimann; Jeff A Cowley; Nicholas M Wade; Yinan Wang; Naga Kasinadhuni; Chon-Kit Kenneth Chan; Jafar S Jabbari; Kirby Siemering; Lavinia Gordon; Matthew Tinning; Juan D Montenegro; Gregory E Maes; et al. (G3: Genes, Genomes, Genetics, 2022)
AbstractShrimp are a valuable aquaculture species globally; however, disease remains a major hindrance to shrimp aquaculture sustainability and growth. Mechanisms mediated by endogenous viral elements have been proposed as a means by which shrimp that encounter a new virus start to accommodate rather than succumb to infection over time. However, evidence on the nature of such endogenous viral elements and how they mediate viral accommodation is limited. More extensive genomic data on Penaeid shrimp from different geographical locations should assist in exposing the diversity of endogenous viral elements. In this context, reported here is a PacBio Sequel-based draft genome assembly of an Australian black tiger shrimp (Penaeus monodonP. monodon